The color of desire ; Hurricane : two plays - Cruz, Nilo (Theatre Communications Group, 2011)
"The words of Nilo Cruz waft from the stage like a scented breeze. They sparkle and prickle and swirl, enveloping those who listen in both specific place and time ... and in timeless passions that touch us all."--The Miami Herald One of the United States' most-produced Cuban American writers, Nilo Cruz employs his signature poetic imagery and vivid language to tender and humorous effect in this pair of his newest works. The Color of Desire, set in 1960 Havana, revolves around a passionate romance between an American businessman and an out-of-work Cuban actress. As the relationship becomes a metaphor for their countries' ruptured love affair, Cruz artfully weds magical realism to a familial story that is touching, harrowing, and funny. In Hurricane, a damaged family-a fire-and-brimstone missionary; his wife, who he saved in more than the spiritual sense; and their adopted son, who seems to have materialized from the ocean-face a shocking crisis when a hurricane ravages their Caribbean town. A celebration of humility, generosity, and kindness, Cruz's play explores the nature of identity, faith, and the redemptive power of love. Nilo Cruz is the author of the Pulitzer Prize-winning Anna in the Tropics, as well as A Park in Our House, A Bicycle Country, Dancing on Her Knees, Night Train to Bolina, Two Sisters and a Piano, and other works.